A proactive system for maritime environment monitoring. Issue 2 (30th January 2016) - Moroni, Davide; Pieri, Gabriele; Tampucci, Marco; Salvetti, Ovidio
Highlights: Real time oil spill monitoring system integrating heterogeneous data sources. A Marine Information System based on an Environmental Decision Support System. Proactive system able to support the monitoring and usage of available resources. Maritime geo-referenced risk maps based on data gathered from different sources. Integrated MIS allowing for data correlation and evaluation among different sources. Abstract: The ability to remotely detect and monitor oil spills is becoming increasingly important due to the high demand of oil-based products. Indeed, shipping routes are becoming very crowded and the likelihood of oil slick occurrence is increasing. In this frame, a fully integrated remote sensing system can be a valuable monitoring tool. We propose an integrated and interoperable system able to monitor ship traffic and marine operators, using sensing capabilities from a variety of electronic sensors, along with geo-positioning tools, and through a communication infrastructure. Our system is capable of transferring heterogeneous data, freely and seamlessly, between different elements of the information system (and their users) in a consistent and usable form. The system also integrates a collection of decision support services providing proactive functionalities. Such services demonstrate the potentiality of the system in facilitating dynamic links among different data, models and actors, as indicated by the performed field tests.